TEACHING SPEAKING : ACTIVITIES TO PROMOTE SPEAKING SKILLS IN EFL CLASSROOMS (Lectio: Journal of Language and Language Teaching, 2021)
Abstract In the last few decades, we have seen how English has demonstrated its growing popularity and got widespread acceptance as a global language. Amazingly, the current English non-native speakers has outnumbered its native speakers. In Indonesia, English is adopted as a foreign language. It is learnt as a school subject and not widely used for communication in the society. Therefore, students have very limited opportunities to practice and use the language to communicate  unlike  those who are in English as a native language and  as  a second language (ESL) contexts who have countless opportunities to use the language for communication. This is a challenging task if we aim to develop the students’ speaking skills. Thus, maximizing classroom time with appropriate activities is one of the best options to choose. Dialogue, surveys, picture description, pictures differences, role play, story completion, and storytelling are appropriate activities to promote the speaking skills. To determine which activities to perform, however, a teacher should consider the students’ level of language proficiency, learning outcomes to be attained, and resources availibility. This consideration is important to ensure the activities being chosen are suitable to students’ proficiency level, productive in developing students’ speaking skills, and operable in local contexts. Keywords: speaking, skills, improve, activities, communication
Keywords: speaking; skills; promote; activities; communciation